(untitled) (Razi Medical Journal, 2025)
Study of autism via a methodical search strategy predominantly through the Scopus database. The search employed terms including "autism," "autism spectrum disorder," "ASD," alongside "cytogenetics," "chromosome," "chromosomal abnormality," "copy number variation," "CNV," and "aneuploidy." The inquiry was confined to English, peer-reviewed publications without temporal limitations. The inclusion criteria emphasized original research, reviews, and case reports that elucidate cytogenetic or chromosomal investigations in persons with autism, encompassing classic karyotyping, aCGH, and SNP arrays, accompanied by explicit descriptions of findings and diagnoses. The exclusion criteria eliminated research focused on single-gene mutations lacking a cytogenetic component, non-English publications, editorials, and studies in which chromosomal mosaicism was a secondary observation. The findings indicated a vigorous scientific production in autism research, with annual publications continuously over 300 from 2021 to 2023; however, a decrease was observed in 2024 and 2025. The United States prominently led in publications, with over 600 documents, followed by Italy, the United Kingdom, China, and Canada. Prominent authors such as J.D. Buxbaum and A. Kolezvon significantly influenced research productivity. The review methodologically emphasized the growing integration of advanced genetic testing, such as Chromosomal Microarray Analysis (CMA), Whole Exome Sequencing (WES), and Whole Genome Sequencing (WGS), in conjunction with behavioral evaluations. Chromosomal Microarray Analysis (CMA) has become the recommended initial genetic assessment, detecting harmful copy number variations (CNVs) in 10-20% of autism spectrum disorder (ASD) cases, with elevated rates among individuals with intellectual disabilities. WES functioned as an ancillary instrument, providing diagnoses in 15-30% of ASD cohorts by identifying de novo pathogenic single-nucleotide variants (SNVs) and copy number variations (CNVs). Whole Genome Sequencing (WGS), albeit costly, provided the most thorough genomic perspective, detecting complex structural variants and copy number variations (CNVs) overlooked by alternative methods.